Long COVID 19 Syndrome: Is It Related to Microcirculation and Endothelial Dysfunction? Insights From TUN-EndCOV Study - Charfeddine, Salma; Ibn Hadj Amor, Hassen; Jdidi, Jihen; Torjmen, Slim; Kraiem, Salma; Hammami, Rania; Bahloul, Amine; Kallel, Nesrine; Moussa, Nedia; Touil, Imen; Ghrab, Aiman; Elghoul, Jamel; et al. (Frontiers in Cardiovascular Medicine, 2021)
The COVID-19 disease is a multisystem disease due in part to the vascular endothelium injury. Lasting effects and long-term sequelae could persist after the infection and may be due to persistent endothelial dysfunction. Our study focused on the evaluation of endothelial quality index (EQI) by finger thermal monitoring with E4 diagnosis Polymath in a large cohort of long COVID-19 patients to determine whether long-covid 19 symptoms are associated with endothelial dysfunction. This is a cross-sectional multicenter observational study with prospective recruitment of patients. A total of 798 patients were included in this study. A total of 618 patients (77.4%) had long COVID-19 symptoms. The mean EQI was 2.02 ± 0.99 IC95% [1.95–2.08]. A total of 397 (49.7%) patients had impaired EQI. Fatigue, chest pain, and neuro-cognitive difficulties were significantly associated with endothelium dysfunction with an EQI <2 after adjustment for age, sex, diabetes, hypertension, dyslipidemia, coronary heart disease, and the severity of acute COVID-19 infection. In multivariate analysis, endothelial dysfunction (EQI <2), female gender, and severe clinical status at acute COVID-19 infection with a need for oxygen supplementation were independent risk factors of long COVID-19 syndrome. Long COVID-19 symptoms, specifically non-respiratory symptoms, are due to persistent endothelial dysfunction. These findings allow for better care of patients with long COVID-19 symptoms.